A novel technique of delivering viral vectors to trigeminal ganglia in rats. (9th January 2017) - Long, Hu; Liao, Lina; Zhou, Yang; Shan, Di; Gao, Meiya; Huang, Renhuan; Yang, Xin; Lai, Wenli
Abstract : The objective of this study was to develop a viable and reliable technique of delivering viral vectors to rat trigeminal ganglia. Adult Sprague‐Dawley rats (200–300 g) were used, and lentiviral vectors containing enhanced green fluorescence protein and calcitonin gene‐related peptide short hairpin RNA (shRNA) were generated. Following general anesthesia, viral vectors were delivered to rat trigeminal ganglia using the technique described in this study. Both X‐ray and micro‐computed tomography (micro‐CT) were employed to verify the position of the needles when injecting the vectors. In vivo fluorescence imaging and immunostaining against enhanced green fluorescence protein were performed to determine the success of viral transduction.The levels of calcitonin gene‐related peptide in trigeminal ganglia were determined using real‐time PCR, and pain levels following injections were evaluated using the Rat Grimace Scale. Our results show that injection needles can be advanced precisely at the trigeminal fossa and that viral vectors can successfully transduce trigeminal ganglia. Moreover, the levels of calcitonin gene‐related peptide at trigeminal ganglia were down‐regulated on day 7 after viral transduction. Pain levels returned to baseline by day 7 following injection. Therefore, we suggest that our trigeminal ganglion‐targeting technique could be used for delivering genes or drugs to rat trigeminal ganglia.